Back Cover: Energy Storage in Strained Organic Molecules: (Spectro)Electrochemical Characterization of Norbornadiene and Quadricyclane (ChemSusChem 12/2016). Issue 12 (14th June 2016) - Brummel, Olaf; Besold, Daniel; Döpper, Tibor; Wu, Yanlin; Bochmann, Sebastian; Lazzari, Federica; Waidhas, Fabian; Bauer, Udo; Bachmann, Philipp; Papp, Christian; Steinrück, Hans‐Peter; Görling, Andreas; et al.
Abstract : The Back Cover figure displays the molecular structures and electrochemical profiles of norbornadiene (red) and quadricyclane (green) as well as the corresponding energy diagram. This pair of isomers can serve to convert solar energy into a chemical form, store it, and when needed release it in a controlled manner as heat. Next goal: direct energy release into electrical current!" More details can be found in the Full Paper by Brummel et al. onpage 1424 in Issue 12, 2016 (DOI:10.1002/cssc.201600127 ).